Transformation of Higher Education Through Digital Leadership (Systematic Literature Review) - Sukandi, Pipin (Ilomata International Journal of Management, 2024)
This research aims to explore the implementation of digital leadership in higher education and its impact on the digital transformation process in the management of higher education institutions. With the rapid development of digital technology, universities are challenged to adopt leadership practices that are aligned with the current digital era. This research uses a systematic literature review method. The results revealed that digital leadership involves the ability to lead digital change, facilitate virtual collaboration, utilize data analytics for decision making, and create a digital culture that is open to innovation. The main challenges faced are resistance to change, limited resources, and data security. Success factors include a clear vision, digital training for leaders and staff, adequate technology infrastructure, and active engagement of all stakeholders.